Plant growth–promoting rhizobacteria: Peribacillus frigoritolerans 2RO30 and Pseudomonas sivasensis 2RO45 for their effect on canola growth under controlled as well as natural conditions - Świątczak, Joanna; Kalwasińska, Agnieszka; Brzezinska, Maria Swiontek (Frontiers in Plant Science, 2024)
Even though canola is one of the most important industrial crops worldwide, it has high nutrient requirements and is susceptible to pests and diseases. Therefore, natural methods are sought to support the development of these plants. One of those methods could be a plant growthpromoting rhizobacteria (PGPR) that have a beneficial effect on plant development. The aim of this study was a genomic comparison of two PGPR strains chosen based on their effect on canola growth: Peribacillus frigoritolerans 2RO30, which stimulated canola growth only in sterile conditions, and Pseudomonas sivasensis 2RO45, which promoted canola growth in both sterile and non-sterile conditions. First of all, six bacterial strains: RO33 (Pseudomonas sp.), RO37 (Pseudomonas poae), RO45 (Pseudomonas kairouanensis), 2RO30 (Peribacillus frigoritolerans), 2RO45 (Pseudomonas sivasensis), 3RO30 (Pseudomonas migulae) demonstrating best PGP traits in vitro were studied for their stimulating effect on canola growth under sterile conditions. P. frigoritolerans 2RO30 and P. sivasensis 2RO45 showed the best promoting effect, significantly improving chlorophyll content index (CCI) and roots length compared to the non-inoculated control and to other inoculated seedlings. Under non-sterile conditions, only P. sivasensis 2RO45 promoted the canola growth, significantly increasing CCI compared to the untreated control and to other inoculants. Genome comparison revealed that the genome of P. sivasensis 2RO45 was enriched with additional genes responsible for ACC deaminase (acdA), IAA (trpF, trpG), and siderophores production (fbpA, mbtH, and acrB) compared to 2RO30. Moreover, P. sivasensis 2RO45 showed antifungal effect against all the tested phytopathogens and harbored six more biosynthetic gene clusters (BGC), including syringomycin, pyoverdin, viscosin, arylpolyene, lankacidin C and enterobactin, than P. frigoritolerans 2RO30. These BGC are well known as antifungal agents; therefore it can be assumed that these BGCs were responsible for the antifungal activity of P. sivasensis 2RO45 against all plant pathogens. This study is the first report describing P. sivasensis 2RO45 as a canola growth promoter, both under controlled and natural conditions, thus suggesting its application in improving canola yield, by improving nutrient availability, enhancing stress tolerance, and reducing environmental impact of farming practices.